Study of the regulatory measures in energy market - T. A. Petrova; V. A. Kardanov (Вестник университета, 2022)
The article examines the problems of Russia’s cooperation in the gas sector within the Eurasian Economic Union, and on the world stage. With the advent of the new millennium, many states began to face more and more questions of their energy security and energy supply. Russia, as one of the world leaders in reserves, production and export of hydrocarbons, constantly faces increased competition at the regional and international levels. As the result, our state has to respond to such a volatile situation in foreign markets by establishing close mutually beneficial cooperation with both producers and consumers of energy resources. Therefore, the incessant changes in the international arena and the emergence of new circumstances leading to problems in the energy sector, makes this study very relevant.